The Implementation of Group Investigation Technique in Teaching Reading of Descriptive Text to the Seventh Graders of SMPN 2 Sidoarjo (RETAIN, 2015)
ABSTRACT The students are expected to have skills of the English language such as reading, writing, listening, and speaking that must be taught to the students through the chosen themes. From those four skills above, reading is the focus of this research. The students should have some purpose or aims from reading that is for getting knowledge and get the meaning of the text. For that reason, a suitable atmosphere of teaching and learning process and a proper technique to conduct the teaching would affect students understanding in reading. Group investigation technique as one of cooperative learning method is an alternative way of organizational approach that allows a class to work actively and collaboratively in small groups and enables students to take an active role in determining their own learning goals and processes. The research design used in this research is a qualitative research. The purpose of this research was to find the description of the implementation of group investigation technique in teaching reading. First, the researcher used observation checklist and field note to answer the first research question. Second, the researcher used interview to answer the second research question. Last, the researcher used reading task to answer the third research questions. According to the observation result, the researcher made conclusion that the group investigation technique can be implemented in the classroom. It could be seen from the students’ task results in the group investigation technique. The students also agreed that the technique was appropriate to be used to teach English in the classroom. Group investigation can be implemented as a technique to teach reading descriptive text to the seventh grader students in SMPN 2 Sidoarjo because this technique is able to make the students more interested in study English. After the implementation of the technique, the students reading comprehension were good. The response of the student towards the technique showed that through group investigation they can communicate and interact more when learning English. Keywords: Group Investigation, Reading, Descriptive, Qualitative Research ABSTRAK Para siswa diharapkan memiliki keterampilan berbahasa Inggris seperti membaca, menulis, mendengarkan, dan berbicara yang harus diajarkan kepada siswa melalui tema tertentu. Dari keempat keterampilan tersebut, membaca adalah fokus dari penelitian ini. Para siswa harus memiliki beberapa tujuan atau bertujuan dari membaca itu adalah untuk mendapatkan pengetahuan dan mendapatkan makna dari teks. Untuk itu, suasana yang cocok dalam proses belajar mengajar dan teknik pengajaran yang tepat untuk melakukan pengajaran dapat mempengaruhi pemahaman siswa dalam membaca. Teknik kelompok investigasi sebagai salah satu metode pembelajaran kooperatif adalah cara pendekatan terorganisasi alternatif yang memungkinkan kelas untuk bekerja secara aktif dan kolaboratif dalam kelompok kecil dan memungkinkan para siswa untuk mengambil peran aktif dalam menentukan tujuan dan proses pembelajaran mereka sendiri. Desain penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Tujuan dari penelitian ini adalah untuk menjabarkan tentang pelaksanaan teknik kelompok investigasi dalam mengajar membaca. Pertama, peneliti menggunakan checklist pengamatan dan catatan lapangan untuk menjawab pertanyaan penelitian yang pertama. Kedua, peneliti menggunakan wawancara untuk menjawab pertanyaan penelitian yang kedua. Terakhir, peneliti menggunakan penugasan membaca untuk menjawab pertanyaan penelitian ketiga. Berdasarkan hasil pengamatan, peneliti membuat kesimpulan bahwa teknik kelompok investigasi dapat diimplementasikan di dalam kelas. Hal ini dapat dilihat dari hasil penugasan siswa melalui teknik kelompok investigasi. Para siswa juga sepakat bahwa teknik ini cocok digunakan untuk mengajar Bahasa Inggris di kelas. Kelompok investigasi dapat diimplementasikan sebagai teknik untuk mengajar membaca teks deskriptif untuk siswa kelas tujuh di SMPN 2 Sidoarjo karena teknik ini mampu membuat siswa lebih tertarik belajar bahasa Inggris. Setelah pelaksanaan teknik tersebut, pemahaman membaca siswa jadi baik. Tanggapan siswa terhadap teknik menunjukkan bahwa melalui kelompok investigasi mereka dapat berkomunikasi dan berinteraksi lebih ketika belajar bahasa Inggris. Kata Kunci: Kelompok Investigasi, Membaca, Deskripsi, Penelitian kualitatif